2020
DOI: 10.20944/preprints202007.0306.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Study the Trend Pattern in COVID-19 using Spline-Based Time Series Model: A Bayesian Paradigm

Abstract: A vast majority of the countries is under the economic and health crises due to the current epidemic of coronavirus disease 2019 (COVID-19). The present study analyzes the COVID-19 using time series, which is an essential gizmo for knowing the enlargement of infection and its changing behavior, especially the trending model. We have considered an autoregressive model with a non-linear time trend component that approximately converted into the linear trend using the spline function. The spline function split th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Splines allow for smooth transitions and subtle structural shifts by piecing together different polynomial line segments, which is an alternative model to deal with the characteristics of COVID-19 case number. Agiwal's study [14] showed spline function is useful to convert the non-linear trend of newly COVID-19 cases into a linear pattern. Sousa et al (2020) [15] proposed an automatic method based on the minimization of the sum of squared residuals plus a penalty to estimate the knot number and locations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Splines allow for smooth transitions and subtle structural shifts by piecing together different polynomial line segments, which is an alternative model to deal with the characteristics of COVID-19 case number. Agiwal's study [14] showed spline function is useful to convert the non-linear trend of newly COVID-19 cases into a linear pattern. Sousa et al (2020) [15] proposed an automatic method based on the minimization of the sum of squared residuals plus a penalty to estimate the knot number and locations.…”
Section: Introductionmentioning
confidence: 99%
“…In his study, spline models outperformed cubic ones with each outcome. Sousa et al[15] and Agiwal et al[14] fitted the daily reported COVID-19 cases of European, American and Asian countries with linear and cubic spline terms, identifying the knots of each country. However, change patterns might be different among various regions in a country.…”
mentioning
confidence: 99%
“…Many applications require piecewise polynomial functions, usually referred to as "splines," which interpolate given data points and satisfy additional conditions such as continuity, smoothness, and convexity or concavity. The recent and the ongoing COVID-19 pandemic, spurred advances in spline-related research, specifically, splines have been shoen to be useful for modeling and forecasting of the COVID-19 spread [1][2][3][4], and COVID-19 trend [5]. In [6], splines were used to analyse the relationship between the ambient temperature and the transmission of COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…Many important applications require interpolation by splines. The recent and ongoing COVID-19 pandemic has spurred advances in spline-related research; specifically, splines have been shown to be useful for modeling and forecasting the spread of COVID-19 [5][6][7][8], and COVID-19 trends [9]. In [10], splines were also used to analyze the relationship between the ambient temperature and the transmission of COVID-19.…”
Section: Introductionmentioning
confidence: 99%